Letter from the Editor - Svensson, Anette (Educare, 2025)
The current issue consists of seven articles covering diverse aspects of educational research such as challenges related to language development, motivation and diversity of proficiency levels among young learners in primary English education; constructions of the disciplinary measure emergency school [Sw. akutskola]; the use of national assessment material for recently arrived students; the construction of children as sedentary, overweight and costly in official documents produced by WHO and OECD; how preschool principals comprehend, practice and develop their pedagogical leadership; possibilities provided by sloyd education for newly arrived students; and Mother Tongue Instruction in secondary school education for students with intellectual disabilities.